Interculturality in Education: paradigms, and proposals from a critical perspective (Journal on studies and research of academic knowledge, 2024)
Nowadays, the majority of laws and syllabus give an importan role to the cultural diversity when they develop curricula. However, the view about diversity is still presented as a problem that must be solved rather uses cualitative analysis to address an interpretation from the anthropology of interculturality in order to analyze, describe and locate the most relevant intercultural discourses and paradigms and their influence on the development of educational policies in the European context as well as in Latin American countries. Another goal is to assess the emerging role that Higher Education must asume as a scenario for intercultural dialogue and empowement with regard to the neoliberal approach of educational inclusión and homogenization. Based on the recognition of the contextual aspect of the concept of interculturality, experiences carried out by several intercultural universities are analysed to determine what challenges arise with regard to the intended transformation of education. As final results, it is highligthed the critical intercultural appoach as a way to make visible the asymmetries and inequalities in the school environment as a means to overcome the dichotomies that “universal knowledge” has meant  for the design of curricula and ways of understanding teaching processes and hegemonic learning. As a conclusión, a series of alternative proposals are put forward in order to create more equal and fair educational environments for all.